“If you want to get ahead, get a Hat”: Manliness, Power, and Politics via the Top Hat - Beaujot, Ariel (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2014)
This paper identifies an important historical and social phenomenon largely neglected by historians: the way in which headwear functioned as a site in the making of class-based masculinities in Victorian British society. Hats were an index to social power and an object from which a narrative could be read. They were also part of the signs and symbols that clarified the public landscape. By focusing on headwear we can assess one of the ways in which power, class, and masculinity were formed and maintained in Victorian Britain. The first half of this article explores the symbolism of hats by focusing on the ways in which they depicted and reinforced elite masculinity and status. The second half looks at the particular arena of the House of Commons where several sartorial issues were tested and resolved. This paper argues that the consolidation of hegemonic elite masculinity is done in what seemed like minor incidents concerning fashion.